Ideological Degradation of Economics versus Changes in the Global Financial Markets (Economic and Political Thought, 2012)
The author presumes that the basic pre-causes of the world financial crisisshould be looked for in macroeconomics. In 1980s, its mainstream, embracingclassical liberalism modified by J.M. Keynes and – to certain degree – byordoliberalism (sometimes improperly included into the neoliberal path), waspushed out and replaced by the Hayek-Friedman neoliberal doctrine. Thatdoctrine was transformed step by step into an ideology causing an essentialdeformation of macroeconomics and neglecting the role of scientific premisesin shaping the world economy. The author argues that neoliberalism wasbased on the false dogma of self-regulation and self-stabilizing capabilitiesof not only individual free market but also inter-market links within any freemarket economy as a whole. The economic policy based on that doctrineled to harmful consequences, particularly on the financial markets taken outfrom the system of proper regulations and empowered with the features ofsupra-state bodies.The mixture of the Austrian school anti-state vision and the Chicagoschool’s hypothesis of rational expectations has brought about improperinterventionism as well as malfunctioning of the market mechanisms. Theresults of that type opened a way for the most radical libertarian vision ofanarcho-capitalism, leading to a complete elimination of the state not onlyfrom the economy but also from the political and social life of the nations.According to the author, an implementation of this vision would meana catastrophe to individual countries but, first of all, to the European Unionas the organization integrating not only markets but also the state institutionsas their regulators. Under these circumstances the author advocates lookingfor new systemic solutions and a new scientific doctrine for economic policy,suggesting synergic liberalism, based on the permanent joint action of thestates and markets in order to achieve synergy effects going beyond theresults of their complementarities or typical interventionism.